The transporter GAT1 plays an important role in GABA-mediated carbon-nitrogen interactions in Arabidopsis - Batushansky, Albert; Kirma, Menny; Grillich, Nicole; Pham, Phuong A.; Rentsch, Doris; Galili, Gad; Fernie, Alisdair R.; Fait, Aaron (Frontiers in Plant Science, 2015)
Glutamate derived γ-aminobutyric acid (GABA) is synthetized in the cytosol prior to delivery to the mitochondria where it is catabolized via the TCA cycle. GABA accumulates under various environmental conditions, but an increasing number of studies show its involvement at the crossroad between C and N metabolism. To assess the role of GABA in modulating cellular metabolism, we exposed seedlings of A. thaliana GABA transporter gat1 mutant to full nutrition medium and media deficient in C and N combined with feeding of different concentrations (0.5 mM and 1mM) of exogenous GABA. GC-MS based metabolite profiling showed an expected effect of medium composition on the seedlings metabolism of mutant and wild type alike. That being said, a significant interaction between GAT1 deficiency and medium composition was determined with respect to magnitude of change in relative amino acid levels. The effect of exogenous GABA treatment on metabolism was contingent on both the medium and the genotype, leading for instance to a drop in asparagine under full nutrition and low C conditions and glucose under all tested media, but not to changes in GABA content. We additionally assessed the effect of GAT1 deficiency on the expression of glutamate metabolism related genes and genes involved in abiotic stress responses. These results suggest a role for GAT1 in GABA-mediated metabolic alterations in the context of the C-N equilibrium of plant cells.